Pendidikan Kewirausahaan dan Ekosistem Kewirausahaan Universitas terhadap Intensi Berwirausaha (Studi pada para Mahasiswa Tingkat Akhir di Kota Medan) - Kiki Sudiana; Ibnu Sina Taher (IPM2KPE, 2024)
This research aims to investigate the influence of entrepreneurship education and the university's entrepreneurial ecosystem on the entrepreneurial intentions of final year students in the city of Medan. The purposive sampling method was used with a sample size of 290 students. This research applies a quantitative approach and is analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary and secondary data were collected through distributing questionnaires, and analyzed using SmartPLS 3.0 software. The research results show that entrepreneurship education and the university's entrepreneurial ecosystem have a positive and significant influence on students' entrepreneurial intentions. These findings provide an important contribution to the development of educational strategies and entrepreneurial ecosystems at universities to encourage interest in entrepreneurship among students, which is expected to be an agent of change in reducing unemployment in the city of Medan. Keywords: University Entrepreneurship Ecosystem, Entrepreneurial Intentions, Entrepreneurship Education This research aims to investigate the influence of entrepreneurship education and the university's entrepreneurial ecosystem on the entrepreneurial intentions of final year students in the city of Medan. The purposive sampling method was used with a sample size of 290 students. This research applies a quantitative approach and is analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary and secondary data were collected through distributing questionnaires, and analyzed using SmartPLS 3.0 software. The research results show that entrepreneurship education and the university's entrepreneurial ecosystem have a positive and significant influence on students' entrepreneurial intentions. These findings provide an important contribution to the development of educational strategies and entrepreneurial ecosystems at universities to encourage interest in entrepreneurship among students, which is expected to be an agent of change in reducing unemployment in the city of Medan. Keywords: University Entrepreneurship Ecosystem, Entrepreneurial Intentions, Entrepreneurship Education